OC-030 Nurse-led discharge support reduces hospital stay and re-admission rates for patients with decompensated chronic liver disease. (17th June 2017) - Martin, M; Dickson, S; Neilson, M; Barclay, S; Forrest, E
Abstract : Introduction: Background: Patients admitted with decompensated chronic liver disease (DCLD) who recover from their immediate illness may experience delayed discharge on account of laboratory abnormalities and titration of diuretics. Readmission is frequent, and often occurs prior to liver outpatient clinic (LOPC) review. Aim: Glasgow Liver Ambulatory Support Service (GLASS), a nurse led discharge pathway for patients with DCLD, was established to reduce length of stay (LOS) and readmission rates. We sought to examine the effectiveness of this approach. Method: The GLASS team reviewed inpatients with DCLD and provided education on liver disease and its treatment, emphasising self-management. On discharge patients were offered GLASS outpatient appointments within 7 days, and were reviewed as necessary until seen at standard LOPC. Appointments allowed blood monitoring; titration of diuretics, arrangement of day case paracentesis and titration of encephalopathy medication. Using ICD discharge codes for DCLD, readmission rates and LOS for primary and readmissions over 3 months during GLASS were calculated and compared with 3 months pre-GLASS. Results: 142 DCLD patients were offered out-patient GLASS review over 9 months: 99 (70%) attended. Comparison of 3 month periods pre and during GLASS demonstrated lower readmission rates (5/57 (8.7%) vs. 8/61 (13.1%)), and median LOS (7 days vs. 8 days) during the GLASS period. Median length of readmission was also shorter (5 days vs. 8 days). Total bed days were reduced from 1034 to 534 (48.7% reduction). Conclusion: A nurse-led discharge service is effective in reducing hospital stay and preventing early readmission for patients with DCLD. Disclosure of Interest: None Declared